The Pengaruh Persepsi Kegunaan dan Dipersonalisasi Pengalaman tentang Loyalitas Merek: Peran Mediasi Merek Keterlibatan di antara Pengguna Duolingo Premium di Indonesia - Lela, Lela; Wenny Pebrianti; Ilzar Daud; Bintoro Bagus Purmono; Ahmadi Ahmadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The rapid development of educational technology-based language learning platforms (EdTech) has transformed digital learning patterns in Indonesia, especially through premium subscription models. This study aims to analyze the influence of Perceived Usefulness and Personalized Experience on Brand Loyalty with Brand Engagement as a mediating variable in Duolingo Premium users in Indonesia. A quantitative approach with a cross-sectional design was used through an online survey of 250 active users who had maintained a minimum of one year subscription. Data analysis was carried out using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that the perception of usability and personalized experience has a positive and significant effect on brand engagement, which in turn has an impact on user loyalty on an ongoing basis. Additionally, Brand Engagement has been shown to significantly mediate the relationship between perceived benefits and personalization on long-term loyalty. These findings indicate that the consistency of functional benefits as well as the quality of personalization of learning are able to drive users' emotional and cognitive engagement. Managerially, the results of the study confirm that the success of a premium platform does not only depend on the completeness of the features, but also on its ability to support the achievement of learning objectives, thereby increasing positive user retention and advocacy.